Stem Diameter Decrement in Holm Oak (Quercus rotundifolia Lam.): Insights into Tree Decline Pathways in Endangered Woodlands of Southern Portugal - Augusta Costa; Ana Cristina Moreira (Ecologies, 2023)
Stem diameter growth in living trees refers to the invariably increase in dimension over a given period. However, reversible stem diameter decrease could occur, related to water movement in the vessels within the wood (on a daily basis) and to tree water deficit and depletion of stored water (on a seasonal basis). Recently, the perennial decrement in stem diameter size has been related to a tree decline pathway, and eventually resulting in tree death. In this study, we analysed stem diameter intra-annual growth dynamics of holm oak (Quercus rotundifolia Lam.) trees for two full growing seasons in distinct woodlands, Laborela and Aldeia dos Fernandes, in southern Portugal (Ourique district). Our focus was to assess stem diameter growth patterns and trends in holm oak trees in endangered woodlands with high tree mortality and to question if perennial decrement. Holm oaks in Laborela were much more sensitive in their stem diameter variations than in Aldeia dos Fernandes and, on average, their stem diameter decreased continuously by 1.0 mm along the 2-year study period, with a slightly higher annual decrease in the first study year (0.6 mm.yr−1). In addition, on average, trees had a higher decrease in stem sectional area of 5.8 cm2 in Laborela against a decrease of 3.7 cm2 in Aldeia dos Fernandes, where the stem diameter of holm oaks only decreased in the first study year (0.1 mm.yr−1). In each study area, the repeated- measures ANOVA showed that tree size effect influenced the stem diameter variations in contrast to tree crown defoliation. Trees were, on average, relatively smaller in Laborela, with DBH = 35.5 cm against DBH = 40.6 cm in Aldeia dos Fernandes, and were highly sensitive in their stem diameter decrement along two consecutives full growing seasons. This is the first exploratory study on assessing the stem diameter fluctuations on holm oaks to address a decline pathway. Our results revealed that holm oaks can survive during two consecutive growing seasons, with a continuous decrease in their stem diameters, which might indicate one tree’s decline pathway.